Basis for Optimal Choice of High Alloyed Structural Materials Used in Chemical and Power Industry - Jiri Kunz; Klara Dalikova; Vladimir Cihal (Communications - Scientific letters of the University of Zilina, 2009)
Six types of high alloyed structural materials widely used especially in power and chemical industry were under study. The experimental programme was focused on the research of materials resistivity against high aggressive media and time variable loading. The paper summarizes results of slow-strain rate test, electrochemical measurements (by means of potentiodynamic method, electrochemical noise measurement and electrochemical impedance spectroscopy) and fatigue test. The investigation was completed by fractographic analysis of failed test specimens. Detailed photo-documentation of specimen fractures was obtained by means of scanning electron microscopy.